Development of Traditional Culinary as a Tourism Attraction in Surakarta City - Annisa, Siti Yumna; Darmawan, Rahmat; Ritonga, Abdul Kadir (Samarinda State Polytechnic, 2023)
The cultural wealth in Surakarta city that has great potential to be developed within the tourism framework is culinary. This article aims to identify the types of traditional food and formulate a program to create traditional food as culinary tourism. The data collection of this article uses direct observation in the field, interviews and documentation studies, while the data analysis uses a SWOT matrix. The results of this study reveal that in the city of Surakarta, there are several types of traditional food, such as Selat Solo, Tengkleng, Timlo Solo, Pecel Ndeso, Gudeg Ceker, Brambang Asem, Krengsengan, Serabi Notosuman, which can be developed as culinary tourism. Tourists' perception of traditional food processing is quite good on the quality of conventional food, food hygiene and service quality. Some programs conducted by the government to develop traditional food are improving the quality of human resources, creating markets for conventional food, identifying potential local products and assessing traditional food. The stall owners also developed programs such as menu adjustment, creativity in conventional food processing, and promotion.